Pretoria Student Law Review 2009-3 (Pretoria University Law Press (PULP), 2010)
Edited by Heinrich Louw, Lynette Osiemo, Ian Learmonth, Francisca Pretorius, Avani Singh and Jared Luke Schultz Assistant Editors: Bronwynne Botha and Tilsetso Makoko 2010